Determinant of training transfer factors towards employees’ performance: a case study at Federal Agriculture Marketing and Authority (FAMA) Kelantan / Nazirah Mohd Asri and Siti Aminah Shahri - Mohd Asri, Nazirah; Shahri, Siti Aminah (2010)
This research was intended to study and identify which factors of training transfer that contributes towards the employee’s performance among employees at FAMA Kelantan. There were two objectives in this research which were to identify the influencing factors of training transfer towards employees’ performance and to explore which influencing factors of training transfer that have strong potential contribution towards employees’ performance. Furthermore, in this research, three factors of training transfer were revealed in literature reviews which are individual characteristics, training design or training characteristics and organizational characteristics or work environment. Under each of three factors of training transfer, there are another two elements that contribute to and have relationship with the employees’ performance. This research was conducted at Federal Agriculture Marketing and Authority (FAMA) Kelantan. The total population is 168, while the sample size is about 50. The respondents were selected by using convenience sampling technique. The questionnaire consist of five sections which are demographic data (Section A) and determinant factors of training transfer towards employees’ performance (Section B, C, D, E). The data was analyzed using Pearson Product Moment Correlation, Descriptive Statistics and Multiple Regression Analysis of Statistical Package for Social Science, (SPSS) version 16.0.